2010
DOI: 10.3329/bmrcb.v36i1.4631
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of fingerprint patterns: An explorative study on beta-thalassemia diagnosis

Abstract: Rapid diagnosis of major β thalassemia along with certain preventive measures is of utmost significance. The present study aims to compare the fingerprints in Major β thalassemic patients (67) and in their parents (76 with minor thalassemia) with the normal fingerprints of control group (144). A forensic medical examiner determined fingerprint types of arch, loop, whorl and other types. Like normal individuals, loop fingerprint pattern was found to be the most common fingerprint type among thalassemic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…In the present study the predominance of ulnar loops over other patterns was noted in both Thalassemia patients and controls and statistically significant difference was found over left digit V (P value .033) [ Table 10]. Similar finding was reported by study of dermatoglyphics of Thalassemics of north-western population by Bhalla et al 8 and in Iranian Thalassemics by Solhi et al [9].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study the predominance of ulnar loops over other patterns was noted in both Thalassemia patients and controls and statistically significant difference was found over left digit V (P value .033) [ Table 10]. Similar finding was reported by study of dermatoglyphics of Thalassemics of north-western population by Bhalla et al 8 and in Iranian Thalassemics by Solhi et al [9].…”
Section: Discussionsupporting
confidence: 79%
“…However, in the present study it was found that the frequency of whorls was increased in Thalassemia patients in comparison to controls [ Table 8] but the difference was found statistically significant for digit IV of left hand (P value .010) and right hand (P value .042) only. Solhi et al [9] also reported increased whorls in all fingers in Thalassemic patients than normal individuals and the number of loop fingerprints was smaller…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors affecting the development of fingerprints towards a regular shape (e.g., size, thickness of subcutaneous fat, degree of stoutness, growth rate of bone) eventually result in the diversity of fingerprints. In general, it is thought that the dermatoglyphic pattern of a human fingertip (whorl, loop or arch) is controlled mainly by genetic factors (Solhi et al 2010; Cheng et al 2009; Dipierri et al 2014), and that its diversification also reflects the genetic diversity of individuals (Madan et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Some relationships have been reported between diseases such as Down syndrome, mental retardation, multiple sclerosis, thalassemia and types of fingerprints. [4][5][6][7][8][9][10][11][12][13][14][15] In our previous study, 16 we showed that there were differences between fingerprint types of women who were carriers of hemophilia and normal, healthy women. Therefore, in the present study we have compared the fingerprint types of the hemophilic patients and the healthy people.…”
Section: Introductionmentioning
confidence: 99%